The Relationship of Utilization of Digital Payment and Customer Satisfaction among DepEd Employees in Digos City - Cervantes, Jade; Armingol, Mike Kiven; Abrasaldo, Kristine; Amit, Diane; Alejandrino, Marlo (Journal of Interdisciplinary Perspectives, 2024)
The research explored the relationship between digital payment utilization and customer satisfaction among DepEd employees in Digos City, with a specific focus on GCash services. It employs a descriptive-correlational design, analyzing responses from 100 DepEd employees to understand this dynamic. The findings indicate a high level of digital payment utilization and customer satisfaction, suggesting that digital payment methods are well-integrated and appreciated by the employees. A significant correlation exists between the frequency of digital payment use and customer satisfaction levels. This emphasizes the need for improved digital payment systems to enhance user experience and security. For instance, simplifying the transactional procedures, enhancing technical protection measures, and increasing the extent of digital payment use are identified as significant predictors of customer satisfaction, highlighting areas for potential improvement to increase satisfaction. The study underscores the importance of continuous innovation in digital payment systems to meet user needs and enhance satisfaction. The implications are particularly relevant for educational institutions transitioning to digital payments, as they can benefit from a more streamlined and secure payment process. The research recommends focusing on transactional efficiency, technical protection, and perceived benefits to improve user satisfaction and adoption rates. By addressing these areas, institutions can ensure that their digital payment systems are more user-friendly and secure, thereby increasing overall satisfaction and adoption. This study highlights the critical role of digital payment systems in modernizing financial transactions within educational institutions. Continuous improvement and innovation in these systems are essential to maintain high levels of user satisfaction and to support the broader adoption of digital payments.